Towards the Spirit of Renewal and Openess: The Roman Catholic Church Reforms and the Global South - Willem Leonardus Turpijn; William Cahyawan; Benny Suwito (Global South Review, 2019)
The Second Vatican Council (1962-1965) has brought change into the Roman Catholic Church. Since that day, various changes has taken place within the Roman Catholic Church. Furthermore, the Roman Catholic Church which has always been associated with the Western world, especially European and North American countries, is and will face the "Global South" phenomenon. Some recent studies have shown this real shift. This study will try to present how the “Global South” phenomenon occurs, and what’s the role of the Roman Catholic Church and also local Church, as well as the opportunity to grow and developed more. Discussing also how the Roman Catholic Church which has been built from a fairly long tradition for around two millennia will face the situation of its universality and also at the same time its diversities and localities as the Church becomes increasingly dominated by Catholics in the Global South region. Some of ideas are the Church should embraces Global South, increasingly develop the spirit of renewal and openness, and the most important thing is to involving the participation of local Church in South Countries to overcome social issues that occurs or we called it a Participatory Church.